Assessing the transcriptional regulation of L-cysteine desulfhydrase 1 in Arabidopsis thaliana - Laureano-Marín, Ana M.; García, Irene; Romero, Luis C.; Gotor, Cecilia (Frontiers in Plant Science, 2014)
Hydrogen sulfide is an important signaling molecule that functions as a physiological gasotransmitter of comparable importance to NO and CO in mammalian systems. In plants, numerous studies have shown that sulfide increases tolerance/resistance to stress conditions and regulates essential processes. The endogenous production of hydrogen sulfide in the cytosol of Arabidopsis thaliana occurs by the enzymatic desulfuration of L-cysteine, which is catalyzed by the L-cysteine desulfhydrase enzyme DES1. To define the functional role of DES1 and the role that the sulfide molecule may play in the regulation of physiological processes in plants, we studied the localization of the expression of this gene at the tissue level. Transcriptional data reveal that DES1 is expressed at all developmental stages and is more abundant at the seedling stage and in mature plants. At the tissue level, we analyzed the expression of a GFP reporter gene fused to promoter of DES1. The GFP fluorescent signal was detected in the cytosol of both epidermal and mesophyll cells, including the guard cells. GFP fluorescence was highly abundant around the hydathode pores and inside the trichomes. In mature plants, fluorescence was detected in floral tissues; a strong GFP signal was detected in sepals, petals and pistils. When siliques were examined, the highest GFP fluorescence was observed at the bases of the siliques and the seeds. The location of GFP expression, together with the identification of regulatory elements within the DES1 promoter, suggests that DES1 is hormonally regulated. An increase in DES1 expression in response to ABA was recently demonstrated; in the present work, we observe that in vitro auxin treatment significantly repressed the expression of DES1.